The meanings of Chinese slangs in Kazakh language - Ершат, А.; Ахметбек, Г. (Journal of Oriental Studies, 2017)
Today, we have so many internet users, including social network users. As we all know, there are no young people who are not familiar with jargons and slangs, which are used by us almost every single day. Slang consists of a lexicon of non- standard words and phrases in a given language. Jargon is a type of language that is used in a particular context and may not be well understood outside of it. The use of jargons and slangs is not only popular among younger in Kazakhstan, but also in China. However, the use of Network Catchwords seems evenmore frequent in China.